Effect of titanium carbonitride (Ti(C, N)) decomposition on failure mechanisms in inconel 617 alloy. Issue 5 (1st April 2015) - Krishna, Ram; Hainsworth, Sarah V.; Gill, Simon P. A.; Atkinson, Helen V.
ABSTRACT: Titanium Carbonitride (Ti(C, N)) decomposition in Inconel 617 alloy creep‐exposed at 650°C for 574 hours is reported using analytical electron microscopy techniques. Cr‐enriched M23 C6 ‐type carbides enveloped in fine gamma prime particles thought to be precipitated from the decomposition reaction are observed in the alloy. The morphology of the M23 C6 carbides is irregular and blocky and the particle size up to 5μm, whereas the morphology of gamma prime particles is mostly spherical and up to 30 nm in size. Intergranular carbides are mostly secondary precipitates of the M23 Cc type (M predominantly Cr) and these respond to solution heat treatment and precipitate on the grain boundaries as a result of ageing. The ability of intragranular MX to decompose is sensitive to the N content, high N resists decomposition. Decomposed intragranular MX provides an excess source of C which can react locally with Cr to form heat treatable intragranular fine Cr23 C6 precipitates. M6 C can segregate in interdendritic locations during melting which may be the reason for high content of Mo in M23 C6 . These precipitates are generally very small and contribute to an additional hardening effect and are the reason for the onset of voiding and cracking along the grain boundaries that ultimately lead to a reduced creep rupture life. Microsc. Res. Tech. 78:336–342, 2015 . © 2015 Wiley Periodicals, Inc.